Employment of Undocumented Immigrants and the Prospect of Legal Status: Evidence from an Amnesty Program - Carlo Devillanova; Francesco Fasani; Tommaso Frattini (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
This paper estimates the causal effect of the prospect of legal status on the employment outcomes of undocumented immigrants. Our identification strategy exploits a natural experiment provided by the 2002 amnesty program in Italy that introduced an exogenous discontinuity in eligibility based on date of arrival. We find that the prospect of legal status significantly increases the employment probability of immigrants that are potentially eligible for the amnesty relative to other undocumented immigrants. The size of the estimated effect is equivalent to about two thirds of the increase in employment that undocumented immigrants in our sample normally experience in their first year after arrival in Italy. These findings are robust to several falsification exercises.
Keywords: F22; J61; K37; 330; Illegal immigration; Natural experiment; Legalization